The new Middle East : what everyone needs to know - Gelvin, James L., 1951- (Oxford : Oxford University Press, 2018)
December 17, 2016 marked the sixth anniversary of the outbreak of the Arab uprisings. In the six years since Muhammad Bouazizi set himself on fire in Tunisia, igniting the uprisings which continue today, the entire Middle East landscape has changed in ways that were unimaginable before. In spite of the early hype about the "Arab Spring" and the prominence observers gave to calls for the downfall of regimes and an end to their abuses, most of the protests and uprisings born of Bouazizi's self-immolation have had disastrous results across the whole Middle East. While the old powers reasserted their control with violence in Egypt and Bahrain, Libya, Yemen, and Syria have virtually ceased to exist as states, torn apart by civil wars. In other states-Morocco and Algeria-the forces of reaction were able to maintain their hold on power, while in the "hybrid democracies"--Lebanon, Palestine, and Iraq-protests against government inefficiency, corruption, and arrogance have done little to bring about the sort of changes protesters have demanded. Simultaneously, ISIS, along with other jihadi groups (al-Qaeda, al-Qaeda affiliates and wannabes, Ansar al-Shariahs, etc.) have thrived in an environment marked by state breakdown. This book explains these changes, outlining the social, political, and economic contours of what some have termed "the new Middle East." One of the leading scholars of modern Middle Eastern history, James L. Gelvin lucidly distills the political and economic reasons behind the dramatic news that come every day from Syria and the rest of the Middle East. He shows how and why bad governance, stagnant economies, poor healthcare, climate change, population growth, refugee crisis, food and water insecurity, and war increasingly threaten human security in the region
Before the deluge : the Middle East, 1945-2011 -- The Arab uprisings and their fallout -- The Syria imbroglio -- The rise and decline of ISIS -- Patrons, proxies, and freelancers : the international relations of the new Middle East -- Human security in the new Middle East.
Includes bibliographical references and index.
Description based on print version record
eBooks on EBSCOhost
Keywords: IS (Organization) -- History; IS (Organization); Middle East -- Politics and government -- 21st century; Middle East -- History; Arab Spring, 2010-; Middle East -- Foreign relations -- 21st century; Human security -- Middle East; Moyen-Orient -- Politique et gouvernement -- 21e siècle.; Moyen-Orient -- Histoire; Printemps arabe, 2010-2011.; Moyen-Orient -- Relations extérieures -- 21e siècle.; HISTORY -- Middle East -- General; Diplomatic relations; Human security; Politics and government; Middle East; Since 2000; History